Sex Differences in the Behavioral and Synaptic Consequences of a Single in vivo Exposure to the Synthetic Cannabimimetic WIN55,212-2 at Puberty and Adulthood - Borsoi, Milene; Manduca, Antonia; Bara, Anissa; Lassalle, Olivier; Pelissier-Alicot, Anne-Laure; Manzoni, Olivier J. (Frontiers in Behavioral Neuroscience, 2019)
Heavy cannabis consumption among adolescents is associated with significant and lasting neurobiological, psychological and health consequences that depend on the age of first use. Chronic exposure to cannabinoid agonists during the perinatal period or adolescence alters social behavior and prefrontal cortex (PFC) activity in adult rats. However, sex differences on social behavior as well as PFC synaptic plasticity after acute cannabinoid activation remain poorly explored. Here, we determined that the consequences of a single in vivo exposure to the synthetic cannabimimetic WIN55,212-2 differently affected PFC neuronal and synaptic functions after 24h in male and female rats during the pubertal and adulthood periods. During puberty, single cannabinoid exposure reduced play behavior in females but not males. In contrast, the same treatment impaired sociability in both sexes at adulthood. General exploration and memory recognition remained normal at both ages and both sexes. At the synaptic level, single cannabinoid exposure ablated endocannabinoid-mediated synaptic plasticity in the PFC of females of both ages and heightened excitability of PFC pyramidal neurons at adulthood, while males were spared. In contrast, cannabinoid exposure was associated with impaired long-term potentiation specifically in adult males. Together, these data indicate behavioral and synaptic sex differences in response to a single in-vivo exposure to cannabinoid at puberty and adulthood.